Branding estratégico para las MiPyMEs del sector calzado de Tungurahua - Villalva Andrade, Sergio Alexander (2024)
This thesis addresses the development of strategic branding strategies for MSMEs in the footwear sector in Tungurahua, a key sector for the local economy. A mixed analysis was carried out through interviews, surveys, focus groups and direct observation in order to identify the scarce application of strategic branding in these enterprises. The results reveal that many MSMEs do not effectively integrate design and brand identity into their strategies, limiting their ability to compete in a saturated market. The proposal includes tailored strategies to improve brand identity, visual communication and customer experience. It is recommended to implement a branding plan that includes a coherent visual identity, strategic design training and emotional narratives to connect with consumers. These strategies seek to improve the positioning and differentiation of Tungurahua's MSMEs, fostering sustainable and competitive growth in the global marke